The influence of curriculum and school climate on the academic attitude of tahfiz students in Malaysia - Muhamad Suhaimi Taat; Roslee Talip; Musirin Mosin (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study aimed to examine the influence of curriculum and school climate on the academic attitude of tahfiz (memorizing Al-Quran) students in Sabah, Malaysia. A total of 81 students (age 10-12) from three private tahfiz primary schools around Kota Kinabalu were involved in this study. This quantitative study used cross-sectional survey method by distributing questionnaires to the respondents. The questionnaire was developed by the researchers to suit the unique environment of the tahfiz schools and has gone through the process of validity and reliability. Descriptive analysis showed that student attitude variable showed a high level of mean score (above 3.80), while for school climate variable, the finding was at moderate level (Mean=3.56, SD=0.530). As for curriculum variable, most students learnt the same main subjects as studied in government-aided primary schools, with addition to Quranic subject. However, no one learnt Computer Education subject. Multiple regression analysis showed that only the school climate variable significantly influenced the academic attitude of tahfiz students (R2=0.251, Beta=0.503, p<0.001). This study will be able to provide useful information and benefit for the improvement of tahfiz institutions in Malaysia.